The use of various genetically engineered biological drugs and selective immunosuppressants within the current provider-payment model of russian diagnosis-related groups - E. V. Derkach; E. A. Pyadushkina; M. V. Avxentyeva; T. V. Boyarskaya; E. E. Yagnenkova; A. S. Mokrova; M. M. Maryanyan (Фармакоэкономика)
Diagnosis-Related Groups (DRG) for the payment for biological therapy were created at the stage of the pilot project and their coefficients of input intensity were not revised since then. The expansion of the range of genetically-engineered biological drugs (GEBD) and the development of new indications for biological therapy and new groups of expensive drugs (like selective immunodepressants, SI) determine the necessity in the differentiated payment for the therapy with GEBD and SI. However, at the federal level, this will be possible only after the approval of the clinical recommendations.Aim. The study aimed to identify possible applications of different GEBD and SI within the current provider-payment model of the Russian diagnosis-related group in terms of bronchial asthma (BA) and inflammatory bowel disease (IBD) - Crohn's disease and ulcerative colitis.Materials and methods. The expenses on GEBD and SI for one case of hospitalization were calculated and compared with the imposed tariffs. For the evaluation of the possibility of the provision of an expensive treatment within the existing DRG model, the authors modeled the distribution of patients with BA and IBD by different pharmaceutical treatment plans in the current practice and cases of an increase in the share of indications of more expensive therapy. The authors identified the number of patients that could have been treated without an increase in the costs of compulsory medical insurance (CHI). The authors proposed the subgroups for the differentiated payment for the treatment of BA and IBD with GEBD and SI.Results. Few variants of treatment with GEBD and SI were characterized by the costs of drugs that would exceed an average payment rate for DRG st36.003 and ds36.004 in 2020. In the model, an increase in the share of patients that received the most expensive drugs of all the registered GEBD and SI in the RF for the treatment of BA and IBD did not lead to an increase in the costs for CHI. It is possible to maintain the initial volume of the financing and increase the number of patients that receive GEBD and SI due to a decrease in the number of hospitalizations. The authors identified approximate values of the coefficient of input intensity (CII) for the subgroups that can be formed for the differentiated payment for pharmaceutical treatment with GEBD and SI.Conclusion. Despite the fact that without the recalculation of CII, there were numerous changed introduced into DRGs st36.003 and ds36.004 “Treatment with GEBD and SI” and the spectrum of the associated clinical situations expanded, it was possible to maintain the possibility of the payment for the therapy with different drugs, including the most expensive ones without an increase in the costs for the CHI system. Still, the results of the present study indicate the necessity in the optimization of the system of payment for medical care with genetically-engineered biologic drugs and selective immunodepressants through the implementation of a differentiated approach to the payment at the federal level.